UPAYA MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMP NEGERI 13 KOTA CIREBON MELALUI PENGGUNAAN ALAT PERAGA PAPAN STATISTIK - Desy Lusiyana; Jajang Rahmatudin; Andini Oktoviani (Integral : Pendidikan Matematika, 2017)
This backgound of the researchis because the low of student’s intellectual mathematicsability. The purpose is for knowing the difference result from increasing student’sintellectual mathematics abilty between student’s learning process by using media of statisticboard and student’s learning process by conventional way (it is used by teachers at school inlearning process). The research is the research of kuasi experiment. The design usesNonequivalent Control Grouph Design. In this research, the population is taken from theninth grade student’s SMPN 13 Cirebon. The technique of taking research sample ispurposive sampling. The sample is ninth grade, 38 students of 9.A that will be used asexperiment class, and 35 students of 9.E as control class. Based on the data of NormalityShapiro – Wilk result test pretest, pos-test and N_Gain in this result are normalitydistribution, and the result of Homogenity Levene’s test, pretest mark, post-test and N_Gainhomogen variety. After data is known normal varienty and homogen, so the next test is thedifference of post test on the average and it uses Inddependent sample t – test. The result ofthis Independent samples t – test has point of (1 – tailed) 0,001<0,05 it means H0 refused.And next the diffence on average test N_Gain and Independent sample t – test is got pointsig (1 – tailed) 0,0015 < 0,05, it is H0 refused. Mean while, based on the result of student’sobservation paper recapitulation get average score 43,43 from scala of 36 very goodcategory.Key Words: Media of statistic board (PANTIK) and mathematic Intellectual